PENANGANAN HAMBATAN EPISTEMOLOGI MATEMATIS SISWA DALAM MATERI PERBANDINGAN MENGGUNAKAN PENDEKATAN RECIPROCAL TEACHING DI SMP - Kamiyo, Angela Janita; Bistari, Bistari; Yani, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to knowing and describe the student’s epistemological obstacle in proportion material before and after being handled using reciprocal teaching approach in grade VII SMP Negeri 8 Pontianak. The method used in this research is analytical descriptive oriented to problem solving. Technique of data collection in this research is test and interview. Tools of data collection in this research is diagnostic test and unstructured interview. Diagnostic test contains 4 question in essay, which each item represents three indicator of epistemological obstacle. The data in this research a greater emphasis on qualitative aspects and focused on student’s epistemological obstacle to solve problem related to proportion material. The result obtained are before being handled using reciprocal teaching approach, students sill have epistemological obstacle. The pencentage of the average student’s score on first diagnostic test is only 53%. After being handled using reciprocal teaching approach, student’s epistemological obstacle are handled properly, can be seen on the average student’s score on second diagnostic test increased to 97%. Keywords: Epistmological Obstacle, Proportion Material, Reciprocal Teaching Approach.